2006
DOI: 10.1016/j.clpt.2005.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Telithromycin, but not montelukast, increases the plasma concentrations and effects of the cytochrome P450 3A4 and 2C8 substrate repaglinide

Abstract: Telithromycin, but not montelukast, increases the plasma concentrations and effects of the cytochrome P450 3A4 and 2C8 substrate repaglinide Background and Objective: The antidiabetic repaglinide is metabolized by cytochrome P450 (CYP) 2C8 and CYP3A4. Telithromycin, an antimicrobial agent, inhibits CYP3A4 in vitro and in vivo. Montelukast, an antiasthmatic drug, is a potent inhibitor of CYP2C8 in vitro. We studied the effects of telithromycin, montelukast, and the combination of telithromycin and montelukast o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 31 publications
0
32
0
1
Order By: Relevance
“…Although montelukast has been identified as a highly potent and selective competitive inhibitor of CYP2C8 in vitro (Walsky et al, 2005a,b), it does not inhibit CYP2C8 in vivo (Jaakkola et al, 2006;Kajosaari et al, 2006;Kim et al, 2007). The lack of an in vivo inhibitory effect suggests that the concentrations of montelukast in hepatocytes are much lower than its K i for CYP2C8 (Ͻ0.15 M), consistent with the small unbound fraction of montelukast in plasma.…”
Section: Introductionmentioning
confidence: 85%
“…Although montelukast has been identified as a highly potent and selective competitive inhibitor of CYP2C8 in vitro (Walsky et al, 2005a,b), it does not inhibit CYP2C8 in vivo (Jaakkola et al, 2006;Kajosaari et al, 2006;Kim et al, 2007). The lack of an in vivo inhibitory effect suggests that the concentrations of montelukast in hepatocytes are much lower than its K i for CYP2C8 (Ͻ0.15 M), consistent with the small unbound fraction of montelukast in plasma.…”
Section: Introductionmentioning
confidence: 85%
“…In another study, the inhibition of CYP2C8 by montelukast was found to be competitive and selective, with reversible inhibition constants (K i ) ranging from 0.0092 to 0.15 mM, depending on the protein concentration used in the incubation (Walsky et al, 2005b). However, despite their strong inhibitory effect on CYP2C8 in vitro, neither montelukast nor zafirlukast affected the pharmacokinetics of CYP2C8 substrate drugs in vivo (Jaakkola et al, 2006b;Kajosaari et al, 2006b;Kim et al, 2007). The lack of in vivo effect is likely explained by their extensive plasma protein binding (.99%) (FDA, 1998;Dekhuijzen and Koopmans, 2002).…”
Section: In Vitro Inhibition and Induction Ofmentioning
confidence: 99%
“…The same study resulted in no fold change in the M2/M4 AUC ratio when the dosing interval was Ͼ24 h, reflecting the CYP2C8 half-life. The CYP3A4 inhibitor telithromycin led to a 4-fold increase in the M2/M1 AUC ratio in comparison with the control (Kajosaari et al, 2006b). …”
Section: In Vitro Kinetic Characteristics Of Repaglinide Metabolites mentioning
confidence: 99%